Galectin-3 administration drives remyelination after hypoxic-ischemic induced perinatal white matter injury - Wang, Qian; Diao, Sihao; Qiu, Han; Gao, Ruiwei; Wang, Minjie; Chen, Qiufan; Xiao, Mili; Li, Zhihua; Chen, Chao (Frontiers in Cellular Neuroscience, 2022)
Hypoxic-ischemic (HI) induced perinatal white matter injury (PWMI) is a major cause of neurologic disabilities characterized by selective oligodendroglial death and myelin disruption. Galectin-3 (Gal-3) modulates postnatal subventricular zone gliogenesis and attenuates ischemic injury. However, the association between Gal-3 and myelin formation still remains unclear. In this study, we first perform Gal-3 knockdown (KD) to identify the importance of Gal-3 on myelin formation. Our results show impeded myelin formation, manifested by Olig2/CC1 (+) mature oligodendrocytes number, expression of oligodendroglial maturation-associated markers (MBP and CNPase), and myelin thickness and integrity. Then we perform recombinant Gal-3 (rGal-3) administration by intracerebroventricular injection. Notably, although rGal-3 administration shows no beneficial effect on oligodendrogenesis and myelin formation under normal condition, our results show that rGal-3 administration attenuates cognitive deficits and drives remyelination after PWMI, which are coupled to signs of enhanced myelin resiliency and cognition. Also, our results indicates that the significant increases in substrates for remyelination of rGal-3 administration are accompanied by enhanced Iba-1 (microglia marker)/ Mrc1 (M2 marker) (+) microglia and decreased Iba-1/ iNOS (M1 marker) (+) microglia. Altogether, our data in this research confirm the association between Gal-3 and myelin formation, underscore its position for the capacity for remyelination and restoration of function, and unveils the efficacy of rGal-3 administration with anti-inflammatory phenotype microglia (M2 microglia) activation. Thus, the findings suggest that Gal-3 plays a significant role in myelin formation and remyelination restoration.